Remnant cholesterol shows inverse and nonlinear associations with leukocyte telomere length and serum α-Klotho, mediated by inflammation and oxidative stress - Xing, Baodi; Yu, Jie; Liu, Yiwen; Gao, Qi; Chen, Xinyue; He, Shuli; Ping, Fan; Xu, Lingling; Li, Wei; Zhang, Huabing; Li, Yuxiu (Frontiers in Endocrinology, 2025)
BackgroundRemnant cholesterol (RC) has been implicated in cardiovascular and metabolic disorders, but its direct associations with biological aging remain unclear. We aimed to examine the relationship between RC and two established aging biomarkers, leukocyte telomere length (LTL) and serum α−Klotho, and to evaluate the potential mediating roles of inflammation and oxidative stress.MethodsThis cross-sectional analysis included 1052 adults from a rural cohort in northern China. Linear regressions and restricted cubic splines (RCS) assessed linear and nonlinear relationships. Mediation models explored the mediating effect of inflammation (TNFα, IL-6, IL-1β) and oxidative stress markers (SOD, 8-OHdG).ResultsParticipants with higher RC levels had lower LTL and α-Klotho levels, along with higher levels of TNFα, IL-6, IL-1β, and SOD. In adjusted linear regression, RC showed negative associations with both LTL and α-Klotho (β[95%CI]: -0.177[-0.262, -0.091] and -0.045[-0.066, -0.024]), independent of conventional lipid profiles. Both relationships were nonlinear (P for nonlinear = 0.001 for LTL; 0.019 for α-Klotho). For LTL, the inverse association was confined to 0.65-1.42 mmol/L (no significant associations outside this range), while for α-Klotho it was observed only below 1.37 mmol/L (no associations above it). TNFα and IL-6 partially mediated the relationship between RC and LTL (17.78% and 14.12%, respectively); while SOD partially mediated the association between RC and α-Klotho (58.18%).ConclusionsRC is inversely and nonlinearly associated with both LTL and α-Klotho, independent of traditional lipid profiles, with inflammation and oxidative stress as partial mediators. From an aging perspective, these cross-sectional findings support increased attention to early RC management alongside traditional lipids.